THE EFFECT OF BANK RISK ON FINANCIAL PERFORMANCE (CASE STUDY PT BANK NEGARA INDONESIA, TBK PERIOD 2018 - 2022) - Anwar Syaferi; Batara Maju Simatupang (Journal of Accounting, Management and Islamic Economics, 2023)
One of the bank financial performance is influenced by bank risk factors. This study aims to determine the effect of banking risk analyzed from credit risk (NPL), market risk (NIM), liquidity risk (LDR) and operational risk (BOPO) on financial performance (ROA) and (ROE) at PT Bank Negara Indonesia, Tbk for the period 2018-2022. The analysis method used is descriptive analysis with a quantitative approach. Hypothesis testing is carried out using the SPSS22 data processing application, to carry out the classical assumption test, multiple linear regression test, correlation test (R), determination coefficient test (R2), partial significance test (t test) and simultaneous significance test (F test). The results showed that partially NPL had no effect on ROA and ROE; NIM had a significant positive effect on ROA and ROE; LDR had a significant positive effect on ROA and ROE; BOPO had no effect on ROA and ROE of PT Bank Negara Indonesia, Tbk for the period 2018-2022. The results also show that NPL, NIM, LDR and BOPO simultaneously have a significant positive effect on ROA and ROE of PT Bank Negara Indonesia, Tbk for the period 2018-2022.